Polyimide film for graphite sheet and graphite sheet produced from the same

The use of a polyimide film with specific low-molecular-weight plasticizers and a controlled carbonization/graphitization process addresses the issues of thermal diffusion coefficient and mass reduction rate in graphite sheet production, resulting in a high-quality graphite sheet.

JP7656717B2Active Publication Date: 2025-04-03PI ADVANCED MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023555800
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-23
Filing Date
2022-03-22
Publication Date
2025-04-03
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

The existing polyimide films used for producing graphite sheets face issues such as a decrease in thermal diffusion coefficient and an increase in mass reduction rate during carbonization and graphitization, especially when plasticizers are used.

Method used

A polyimide film containing a first plasticizer and a second plasticizer with molecular weights of 700 g/mol or less is used, along with a method of carbonizing, graphitizing, or both, to produce a graphite sheet with improved thermal diffusion coefficient and reduced mass reduction rate.

Benefits of technology

The proposed solution maintains the thermal diffusion coefficient and appearance quality of the graphite sheet while reducing the mass reduction rate, resulting in a high-quality graphite sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656717000002
    Figure 0007656717000002
  • Figure 0007656717000003
    Figure 0007656717000003
  • Figure 0007656717000004
    Figure 0007656717000004
Patent Text Reader

Abstract

The present invention discloses a polyimide film including a first plasticizer and a second plasticizer, the first plasticizer and the second plasticizer each having a molecular weight of 700 g / mol or less, a method for producing a graphite sheet using the polyimide film, and a graphite sheet having excellent appearance produced from the polyimide film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide film for a graphite sheet and a graphite sheet produced therefrom. [Background technology]

[0002] Recently, electronic devices have become lighter, smaller, thinner, and more highly integrated, which causes a lot of heat to be generated in the electronic devices. Such heat can shorten the lifespan of the product and can cause breakdowns and malfunctions. Therefore, thermal management for electronic devices has emerged as an important issue.

[0003] Graphite sheets have a higher thermal conductivity than metal sheets such as copper and aluminum sheets, and have been attracting attention as a heat dissipation material for electronic devices.

[0004] Graphite sheets can be produced in a variety of ways, for example, by carbonizing and graphitizing a polymer film. In particular, polyimide films have been in the spotlight as polymer films for producing graphite sheets due to their excellent mechanical, thermal, dimensional and chemical stability.

[0005] Various additives can be used in polyimide films used in producing graphite sheets. Among them, plasticizers are widely used to improve the physical properties of polyimide films. However, when a polyimide film containing a plasticizer is converted into a graphite sheet, problems such as deterioration in thermal diffusion coefficient and appearance quality occur, and a solution to these problems is required.

[0006] In addition, efforts are currently being made to find solutions to the problem of increased mass loss during carbonization and graphitization to produce graphite sheets, depending on the type of plasticizer used. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Republic of Korea Patent Publication No. 2017-0049912 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a polyimide film containing a first plasticizer and a second plasticizer, which does not deteriorate in thermal diffusion coefficient and appearance quality even when converted into a graphite sheet, and has a low mass loss rate upon carbonization and graphitization.

[0009] Another object of the present invention is to provide a method for producing a graphite sheet from said polyimide film and a graphite sheet of excellent quality produced therefrom. [Means for solving the problem]

[0010] In order to achieve the above object, one embodiment of the present invention includes a first plasticizer and a second plasticizer, The molecular weight of the first plasticizer and the second plasticizer is 700 g / mol or less. A polyimide film is provided.

[0011] Another embodiment of the present invention includes the step of carbonizing, graphitizing, or carbonizing and graphitizing the polyimide film. A method for producing a graphite sheet is provided.

[0012] Yet another embodiment of the present invention provides a graphite sheet manufactured by the above-described method for manufacturing a graphite sheet. Effect of the Invention

[0013] The present invention has an effect of providing a polyimide film which does not decrease in thermal diffusion coefficient and has a low mass loss rate upon carbonization and graphitization, a method for producing a graphite sheet from the polyimide film, and a graphite sheet having excellent appearance produced from the polyimide film. [Brief description of the drawings]

[0014] [Figure 1] 1 is a graph showing the elongation and strength of polyimide films according to examples and comparative examples of the present invention. [Diagram 2] 1 is a graph showing the true density of polyimide films according to examples of the present invention and comparative examples. [Diagram 3] 1 is a graph showing the thermal decomposition characteristics of polyimide films according to examples and comparative examples of the present invention. [Figure 4] 1 is a graph showing the thermal diffusion coefficient and foam thickness of graphite sheets according to examples and comparative examples of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the embodiments and examples of the present invention will be described in detail so that those skilled in the art can easily carry out the present invention. However, the present invention can be realized in various different forms and is not limited to the embodiments and examples described herein. Throughout this specification, when a part "includes" a certain element, this means that it can further include other elements, not excluding other elements, unless otherwise specified.

[0016] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise.

[0017] When interpreting elements, they are interpreted as including error ranges even if there is no explicit statement to the contrary.

[0018] In this specification, the "to" in the expression "a to b" indicating a numerical range is defined as ≧a and ≦b.

[0019] The polyimide film according to an embodiment of the present invention may include a first plasticizer and a second plasticizer, and the first plasticizer and the second plasticizer may have a molecular weight of 700 g / mol or less.

[0020] For example, the molecular weight of the first plasticizer and the second plasticizer may be, but is not limited to, 700 g / mol or less, 600 g / mol or less, 500 g / mol or less, 450 g / mol or less, 400 g / mol or less, or 370 g / mol or less.

[0021] In general, a plasticizer increases the distance between polyimide polymer chains, weakening the attractive force between polymer chains and shifting the glass transition temperature (Tg) to a lower temperature region.

[0022] If the molecular weight of the plasticizer contained in the polyimide film exceeds 700 g / mol, a problem occurs in that the thermal diffusion coefficient of the graphite sheet decreases when the polyimide film is converted into a graphite sheet.

[0023] It is presumed that such a decrease in the thermal diffusion coefficient occurs because, as the molecular weight of a plasticizer increases, the plasticizer molecules increase the distance between polyimide molecular chains in the polyimide film, thereby affecting the graphite sheet manufactured from the polyimide film.

[0024] Furthermore, if the molecular weight of the plasticizer in the polyimide film is less than 250 g / mol, the mass loss rate during carbonization and graphitization of the polyimide film for producing the graphite sheet will be high.

[0025] It is presumed that such a change in mass loss rate occurs because, as the molecular weight of a plasticizer decreases, the attractive force between plasticizer molecules or between a plasticizer and a polyimide molecule decreases, resulting in increased volatility, which prevents the plasticizer from properly functioning as a plasticizer in the film when the polyimide film is carbonized and graphitized to produce a graphite sheet.

[0026] That is, when a polyimide film contains only one type of plasticizer, it is difficult to solve both the problems of a low thermal diffusion coefficient and a high mass loss rate. However, when a polyimide film contains two or more types of plasticizers with different molecular weights, it is possible to ensure both a high thermal diffusion coefficient and a low mass loss rate during carbonization and graphitization of the polyimide film by appropriately adjusting the types and ratio of the plasticizers during graphite conversion.

[0027] In one embodiment, the difference in molecular weight between the first plasticizer and the second plasticizer may be 150 g / mol or less.

[0028] For example, the difference in molecular weight between the first plasticizer and the second plasticizer may be, but is not limited to, 150 g / mol or less, 120 g / mol or less, 100 g / mol or less, or 50 g / mol or less.

[0029] In one embodiment, the polyimide film may contain 1.65 wt % or less of the first plasticizer and the second plasticizer based on the total content of the imidization catalyst contained in the polyimide film.

[0030] That is, when the total content of the imidization catalyst contained in the polyimide film is taken as 100% by weight, the total content of the first plasticizer and the second plasticizer contained in the polyimide film may be 1.65% by weight or less.

[0031] For example, the total content of the first plasticizer and the second plasticizer contained in the polyimide film may be 1.65% by weight or less, 1.1% by weight or less, or 0.7% by weight or less.

[0032] The imidization catalyst promotes a ring-closing reaction of polyamic acid, and examples of the imidization catalyst include aliphatic tertiary amines, aromatic tertiary amines, and heterocyclic tertiary amines. Among these, heterocyclic tertiary amines can be used from the viewpoint of reactivity as a catalyst.

[0033] Examples of heterocyclic tertiary amines include quinoline, isoquinoline, β-picoline, pyridine, etc., which can be used alone or in combination of two or more. The imidization catalyst is added in an amount of 0.05 mol to 3 mol (e.g., 0.2 mol to 2 mol) per mol of amic acid group in the polyamic acid, and within the above range, sufficient imidization is possible and it is advantageous for casting into a film, but the amount is not limited thereto.

[0034] If the total content of the first plasticizer and the second plasticizer exceeds 1.65 wt %, the thermal diffusion coefficient decreases and the foaming rate increases when converted into graphite sheets.

[0035] Also, with an increase in the plasticizer content, the density decreases when converted into polyimide film and graphite sheet.

[0036] In one embodiment, the weight ratio of the first plasticizer to the second plasticizer may be 1:9 to 9:1.

[0037] As the specific gravity of the plasticizer with a relatively large molecular weight in the total plasticizer content (content of first plasticizer + content of second plasticizer) increases, the thermal diffusion coefficient of the graphite sheet decreases and the foaming ratio (foaming thickness) tends to increase.

[0038] In addition, as the specific gravity of the plasticizer with a relatively large molecular weight in the total plasticizer content (content of the first plasticizer + content of the second plasticizer) increases, the density of the polyimide film and the graphite sheet tends to increase and then decrease.

[0039] By adjusting the weight ratio of the plasticizer having a relatively large molecular weight to the plasticizer having a relatively small molecular weight in the total content of the plasticizer, the thermal diffusion coefficient, expansion rate, and true density of the graphite sheet can be appropriately adjusted.

[0040] In one embodiment, the first plasticizer and the second plasticizer may be phosphorus (P)-based plasticizers, which may also exhibit flame retardant properties.

[0041] In one embodiment, the first plasticizer or the second plasticizer may be any one selected from the group consisting of triphenyl phosphate, tricresyl phosphate, and triphenylphosphine, resorcinol bis(diphenyl phosphate), and bisphenol A bis(diphenyl phosphate).

[0042] In one embodiment, the polyimide film is manufactured by imidizing a polyamic acid formed by the reaction of a dianhydride monomer and a diamine monomer, and the polyamic acid may have a weight average molecular weight of 100,000 to 500,000. In this range, graphitization is easy when manufacturing a graphite sheet. Here, the "weight average molecular weight" can be measured using gel permeation chromatography (GPC) with polystyrene as a standard sample. The weight average molecular weight of the polyamic acid may be, for example, 150,000 to 500,000, as another example, 100,000 to 400,000, and as yet another example, 250,000 to 400,000, but is not limited thereto.

[0043] As the dianhydride monomer and the diamine monomer, various monomers commonly used in the field of polyimide film manufacturing can be used. For example, the dianhydride monomer may be an aromatic dianhydride monomer, and the diamine monomer may be an aromatic diamine monomer. Dianhydride monomers include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, oxydiphthalic dianhydride, diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylenebis(trimellitic monoester anhydride), p-bi Examples of the dianhydride that can be used include, but are not limited to, phenylene bis(trimellitic acid monoester anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride, or combinations thereof. The diamine monomer includes diamine monomers having one benzene ring (e.g., 1,4-diaminobenzene, 1,3-diaminobenzene, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid, etc.), diamine monomers having two benzene rings (e.g., diaminodiphenyl ethers such as 4,4'-diaminodiphenyl ether and 3,4'-diaminodiphenyl ether, 4,4'-Diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethylbenzidine, 2,2' -Dimethylbenzidine, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone , 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl diamine monomers containing three benzene rings (e.g., 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-Diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-Diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide)benzene, 1,3-bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl )isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, etc.), diamine monomers containing four benzene rings (e.g., 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, phenyl] ether, bis[4-(3-aminophenoxy)phenyl] ether, bis[4-(4-aminophenoxy)phenyl] ether, bis[3-(3-aminophenoxy)phenyl] ketone, bis[3-(4-aminophenoxy)phenyl] ketone, bis[4-(3-aminophenoxy)phenyl] ketone, bis[4-(4-aminophenoxy)phenyl] ketone, bis[3-(3-aminophenoxy)phenyl] sulfide, bis[3-(4-aminophenoxy)phenyl] sulfide, bis[4-(3-aminophenoxy)phenyl] sulfide sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, etc., or combinations thereof can be used, but are not limited thereto.

[0044] In particular, the dianhydride monomer may be pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, oxydiphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof, and the diamine monomer may be 4,4'-oxydianiline, 3,4'-oxydianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-methylenedianiline, 3,3'-methylenedianiline, or a combination thereof.

[0045] The thickness of the polyimide film may be 25 to 500 μm, for example, 25 to 125 μm, or another example, 40 to 500 μm, but is not limited thereto.

[0046] The polyimide film can be manufactured by various methods commonly used in the field of polyimide film manufacturing. For example, the polyimide film can be manufactured by polymerizing one or more dianhydride monomers and one or more diamine monomers in a solvent to prepare a polyamic acid solution, adding an imidization catalyst, a dehydrating agent, and optionally a sublimable inorganic filler, a solvent, etc. to the polyamic acid solution to form a composition for polyimide film, and forming the composition into a film, but the method is not limited thereto.

[0047] The polyamic acid solution is imidized by a known imidization method such as a thermal imidization method, a chemical imidization method, or a hybrid imidization method that combines the thermal imidization method and the chemical imidization method.

[0048] The average particle size (D 50 ) may be 0.1 to 5.0 μm, and the total content of the sublimable inorganic filler may be 0.07 to 0.4% by weight based on the total weight of the polyimide film.

[0049] The sublimable inorganic filler can induce a certain foaming phenomenon by sublimating during carbonization and / or graphitization of the polyimide film. Such foaming facilitates the exhaust of sublimation gases generated during carbonization and / or graphitization, thereby enabling a high-quality graphite sheet to be obtained, and the certain voids formed by foaming can also improve the bending resistance ("flexibility") of the graphite sheet.

[0050] However, excessive foaming and the resulting large number of voids can significantly deteriorate the thermal conductivity and mechanical properties of the graphite sheet and can cause defects on the surface of the graphite sheet, so the type, content and particle size of the sublimable inorganic filler must be carefully selected.

[0051] "Average particle size (D 50) can be measured using a laser diffraction particle size analyzer (SALD-2201, Shimadzu) after ultrasonically dispersing the sublimable inorganic filler in a dimethylformamide solvent at 25°C for 5 minutes.

[0052] The average particle size (D 50 ) may be, for example, 0.5 to 4.0 μm, for example, 0.1 to 2.5 μm, for example, 1.5 to 5.0 μm, for example, less than 1.5 to 2.5 μm, but is not limited thereto. The total content of the sublimable inorganic filler in the polyimide film may be, for example, 0.07 to 0.35 wt %, for example, 0.1 to 0.3 wt %, for example, 0.15 to 0.3 wt %, based on the total weight of the polyimide film, but is not limited thereto.

[0053] The sublimable inorganic filler has an average particle size (D 50 ) of 0.1 to 2.0 μm and a first sublimable inorganic filler having an average particle size (D 50 ) may contain a second sublimable inorganic filler having a size of more than 2.0 to 5.0 μm.

[0054] The content of the first sublimable inorganic filler and the second sublimable inorganic filler in the sublimable inorganic filler is not particularly limited, but for example, based on the total weight of the sublimable inorganic filler, the first sublimable inorganic filler is contained in 90 to 10 weight%, and the second sublimable inorganic filler is contained in 10 to 90 weight%. For example, based on the total weight of the sublimable inorganic filler, the content of the first sublimable inorganic filler may be, for example, 15 to 85 weight%, another example, 20 to 80 weight%, yet another example, 30 to 80 weight%, yet another example, 50 to 80 weight%, and the content of the second sublimable inorganic filler may be, for example, 85 to 15 weight%, another example, 80 to 20 weight%, yet another example, 70 to 20 weight%, yet another example, 50 to 20 weight%, but is not limited thereto.

[0055] Examples of the sublimable inorganic filler include, but are not limited to, calcium carbonate, dibasic calcium phosphate, barium sulfate, and the like.

[0056] The solvent is not particularly limited as long as it can dissolve the polyamic acid. For example, the solvent may include an aprotic polar solvent.

[0057] In particular, sulfoxide solvents such as dimethyl sulfoxide and diethyl sulfoxide; formamide solvents such as N,N-dimethylformamide and N,N-diethylformamide; acetamide solvents such as N,N-dimethylacetamide and N,N-diethylacetamide; pyrrolidone solvents such as N-methyl-2-pyrrolidone and N-vinyl-2-pyrrolidone; phenol solvents such as phenol, o-, m-, or p-cresol, xylenol, halogenated phenols, and catechol; and aprotic polar solvents such as hexamethylphosphoramide and γ-butyrolactone; and the like can be used alone or in combination of two or more kinds, but are not limited thereto.

[0058] The dehydrating agent may be, but is not limited to, acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride, or the like, either alone or in combination.

[0059] The film formation is carried out by applying a polyamic acid solution onto a substrate in the form of a film, heating and drying the solution at a temperature of 30 to 200°C for 15 seconds to 30 minutes to produce a gel film, and then removing the substrate from the gel film and heat-treating the gel film at a temperature of 250 to 600°C for 15 seconds to 30 minutes, but is not limited to this.

[0060] In one embodiment, the polyimide film has an elongation of 120% or more, a strength of 210 MPa or more, a residue amount upon thermal decomposition at 1000° C. of 56% by weight or more, and a true density of 1.35 g / cm 3 It may be more than that.

[0061] The polyimide film may have an elongation of 135% or less and a strength of 230 MPa or less, and the true density of 1.55 g / cm 3 It may be the following.

[0062] As the specific gravity of the plasticizer with a relatively large molecular weight in the total plasticizer content (content of first plasticizer + content of second plasticizer) increases, the elongation and strength tend to decrease slightly.

[0063] In addition, as the proportion of plasticizers with relatively large molecular weights in the total plasticizer content (content of first plasticizer + content of second plasticizer) increases, the amount of plasticizers remaining after thermal decomposition at 1000°C tends to increase.

[0064] If the true density of the polyimide film is low, the rearrangement of carbon during the graphitization process is unfavorable, resulting in low thermal conductivity. If the true density is too high, the graphite sheet may have a poor appearance due to excessive compactness.

[0065] "True density" is the density in which all closed and open pores have been removed, and differs from apparent density, in which open pores have been removed but closed pores are included.

[0066] The true density of the polyimide film can be controlled by various methods, including, but not limited to, controlling the molecular weight of polyamic acid, which is a precursor of the polyimide film, controlling the viscosity by adding a solvent to the polyamic acid, and controlling the type, particle size, and content of a filler contained in the polyimide film.

[0067] In one embodiment, the polyimide film may be for use in producing graphite sheets.

[0068] When a graphite sheet is manufactured using the polyimide film, it is possible to adjust the reduction in thermal diffusion coefficient, mass reduction rate, and expansion rate, and thus it is possible to manufacture a graphite sheet with excellent properties.

[0069] A method for producing a graphite sheet according to another aspect of the present invention includes the step of carbonizing, graphitizing, or carbonizing and graphitizing the polyimide film.

[0070] The carbonization is a process of pyrolyzing the polymer chains of the polyimide film to form a preliminary graphite sheet containing an amorphous carbon body, a non-crystalline carbon body, and / or an amorphous carbon body, and may include, but is not limited to, a step of heating and maintaining the temperature of the polyimide film from room temperature to a maximum temperature in the range of 1,000°C to 1,500°C under reduced pressure or in an inert gas atmosphere for 10 to 30 hours. Optionally, in order to achieve high carbon orientation, pressure may be applied to the polyimide film during carbonization using a hot press, etc., and the pressure may be, for example, 5 kg / cm. 2 The above is another example of 15kg / cm 2 The above is another example of 25kg / cm 2 It may be more than this, but is not limited to this.

[0071] The graphitization is a process of forming a graphite sheet by rearranging carbon in an amorphous carbon body, non-crystalline carbon body, and / or amorphous carbon body, and may include, but is not limited to, a step of selectively heating and maintaining a temperature of a preliminary graphite sheet from room temperature to a maximum temperature of 2,500°C to 3,000°C in an inert gas atmosphere for 2 hours to 30 hours. Optionally, in order to achieve high carbon orientation, pressure may be applied to the preliminary graphite sheet during graphitization using a hot press or the like, and the pressure may be, for example, 100 kg / cm. 2 The above is another example of 200kg / cm 2 The above and further examples are 300kg / cm 2 It may be more than this, but is not limited to this.

[0072] A graphite sheet according to still another aspect of the present invention is manufactured by the above-mentioned graphite sheet manufacturing method, and has a thermal diffusion coefficient of 720 mm 2 / s or more, and the foam thickness may be 85 μm or less.

[0073] The thermal diffusion coefficient is 780 mm 2 / s or less, and the foam thickness may be 60 μm or more.

[0074] Excessive foaming during the carbonization and graphitization processes is undesirable because it can cause damage to the internal structure of the graphite sheet, thereby reducing the thermal conductivity of the graphite sheet and significantly increasing the number of bright spots, which are foaming marks, on the surface of the graphite sheet. EXAMPLES

[0075] The present invention will be described in more detail below with reference to examples. However, these are presented as preferred examples of the present invention and should not be construed as limiting the present invention in any sense.

[0076] Production Example 1 (Production of Polyimide Film) 205.0 g of dimethylformamide was added as a solvent to a reactor, and the temperature was adjusted to 20° C. 21.5 g of 4,4′-oxydianiline (ODA) as a diamine monomer was added thereto, and then 23.4 g of pyromellitic dianhydride (PMDA) as a dianhydride monomer was added thereto to prepare a polyamic acid solution having a viscosity of 230,000 cP.

[0077] Next, 39.5 g of acetic anhydride as a dehydrating agent, 4.8 g of β-picoline as an imidizing agent, and 2-calcium phosphate (average particle size (D 50 0.12 g of 2.5 μm polyimide (Poly(2,5-diaminophenyl)propanediol) and 30.4 g of dimethylformamide were mixed.

[0078] Also, appropriate amounts of a first plasticizer (triphenyl phosphate, TPP) and a second plasticizer (tricresyl phosphate, TCP) were added to prepare a polyimide film precursor solution.

[0079] The prepared polyimide film precursor solution was cast to a thickness of 500 μm on a SUS plate (100SA, Sandvik) using a doctor blade and dried at a temperature range of 100° C. to 200° C. to produce a gel film having self-supporting properties.

[0080] Next, the gel film was peeled off from the SUS plate, fixed to a pin frame, and transported to a high-temperature tenter. The film was heated from 200 to 700°C in the high-temperature tenter, cooled to 25°C, and then separated from the pin frame to obtain a polyimide film.

[0081] Manufacturing Example 2 (Manufacturing of Graphite Sheet) The polyimide film produced in Production Example 1 was heated to 1,210° C. at a rate of 3.3° C. / min under nitrogen gas using an electric furnace capable of carbonization, and was maintained at 1,210° C. for about 2 hours (carbonization).

[0082] Next, a first firing step was carried out by using a graphitizable electric furnace and increasing the temperature from 1,210°C to 2,200°C at a heating rate of 2.5°C / min under argon gas.

[0083] After reaching 2,200°C, the heating rate was changed to 1.25°C / min and the temperature was continuously increased up to 2,500°C to perform the second firing step.

[0084] After reaching 2,500°C, the heating rate was changed to 10°C / min and the temperature was continuously raised to 2,800°C to perform the third firing step. After leaving the mixture at 2,800°C for several minutes, graphitization was completed and graphite sheets were produced.

[0085] Finally, the graphite sheet was cooled at a rate of 10° C. / min.

[0086] Example 1 When a polyimide film was produced according to Preparation Example 1, the first plasticizer and the second plasticizer were added in amounts of 0.47 wt % and 0.08 wt %, respectively, based on the total content of the imidization catalyst mixed in the polyamic acid solution (when the total content of the imidization catalyst is taken as 100 wt %). Then, a graphite sheet was produced according to Preparation Example 2.

[0087] Example 2 A graphite sheet was prepared in the same manner as in Example 1, except that the first plasticizer and the second plasticizer were added in amounts of 0.39 wt % and 0.17 wt %, respectively, based on the total content of the imidization catalyst mixed in the polyamic acid solution.

[0088] Example 3 A graphite sheet was prepared in the same manner, except that the first plasticizer and the second plasticizer were added in amounts of 0.28 wt % and 0.28 wt %, respectively, based on the total content of the imidization catalyst mixed in the polyamic acid solution.

[0089] Example 4 A graphite sheet was prepared in the same manner as in Example 1, except that the first plasticizer and the second plasticizer were added in amounts of 0.17 wt % and 0.39 wt %, respectively, based on the total content of the imidization catalyst mixed in the polyamic acid solution.

[0090] Comparative Example 1 A graphite sheet was produced in the same manner as in Example 1, except that the first plasticizer and the second plasticizer were not added.

[0091] Comparative Example 2 A graphite sheet was prepared in the same manner as in Example 1, except that the first plasticizer was not added, and only the second plasticizer was added in an amount of 0.56 wt % based on the total content of the imidization catalyst mixed in the polyamic acid solution.

[0092] Comparative Example 3 A graphite sheet was prepared in the same manner as in Example 1, except that no second plasticizer was added and only the first plasticizer was added in an amount of 0.56 wt % based on the total content of the imidization catalyst mixed in the polyamic acid solution.

[0093] The contents of the first plasticizer and the second plasticizer in Examples 1 to 4 and Comparative Examples 1 to 3 are as shown in Table 1 below.

[0094] [Table 1]

[0095] Experimental Example 1 The elongation and strength of the polyimide films of Examples 1 to 4 and Comparative Examples 1 to 3 produced in Production Example 1 were measured.

[0096] The elongation and strength were measured using Autograph Universal Testing Machines (Shimadzu, AG-IS) according to the method of ASTM D882.

[0097] As shown in FIG. 1, the elongation and strength of the polyimide films of Examples 1 to 4, in which the first plasticizer and the second plasticizer were mixed, were all increased compared to the polyimide film of Comparative Example 1, which did not contain the first plasticizer and the second plasticizer.

[0098] The polyimide films of Comparative Examples 2 and 3, which contained only the first plasticizer and the second plasticizer, also showed a tendency for all of their elongation and strength to be increased compared to the polyimide film of Comparative Example 1. The polyimide films of Examples 1 to 4, which contained a mixture of the first and second plasticizers, all showed increased elongation and strength compared to the polyimide film of Comparative Example 2, which contained only the first plasticizer, but the strength was slightly lower and the elongation was similar or higher than the polyimide film of Comparative Example 3, which contained only the second plasticizer.

[0099] Specifically, in the case of Examples 1 to 4, the strength was measured to be in the range of 215 to 225 MPa, and the elongation was measured to be in the range of 120 to 135%.

[0100] As the specific gravity of the second plasticizer (TCP) increases in the total plasticizer content (content of first plasticizer + content of second plasticizer), the elongation and strength of the polyimide film show a tendency to decrease partially, although the change is not significant.

[0101] Experimental Example 2 The true density of the polyimide films of Examples 1 to 4 and Comparative Examples 1 to 3 produced in Production Example 1 was measured.

[0102] The true density was measured on a test piece cut into a size of 15 mm x 300 mm (horizontal x vertical) from the prepared polyimide film using a Pycnometer (AccuPyc1340, Micromeritics) at room temperature using helium gas.

[0103] As shown in FIG. 2, in the case of the polyimide films of Examples 1 to 4, the true density range was 1.45 to 1.47 g / cm 3 was measured.

[0104] As the specific gravity of the second plasticizer (TCP) increases in the total plasticizer content (content of first plasticizer + content of second plasticizer), the true density of the polyimide film gradually increases and then decreases.

[0105] In contrast, the true density of the polyimide films of Comparative Examples 1 and 2 was excessively high compared to the true density of the polyimide films of Examples 1 to 4, resulting in a problem of poor appearance of the produced graphite sheet.

[0106] Experimental Example 3 The thermal decomposition characteristics of the polyimide films of Examples 1 to 4 and Comparative Example 1 produced in Production Example 1 were measured.

[0107] The thermal decomposition characteristics were measured using Thermogravimetric Analysis (TA Instruments, TGA5500) by increasing the temperature up to 1000°C at a rate of 10°C / min.

[0108] As shown in FIG. 3, compared to the polyimide film of Comparative Example 1 which did not contain the first plasticizer and the second plasticizer, the polyimide films of Examples 1 to 4 in which the first plasticizer and the second plasticizer were mixed all showed increased amounts of residues upon thermal decomposition at 1000°C.

[0109] In the cases of Examples 1 to 4, the residual amount upon pyrolysis at 1000° C. was measured to be 56% by weight or more.

[0110] As the specific gravity of the second plasticizer (TCP) in the total plasticizer content (content of first plasticizer + content of second plasticizer) increases, the residual amount tends to increase slightly.

[0111] Experimental Example 4 The thermal diffusion coefficients and foam thicknesses of the graphite sheets of Examples 1 to 4 and Comparative Examples 2 and 3 produced by Production Example 2 were measured.

[0112] In the cases of Examples 1 to 4, the thermal diffusion coefficient of the produced graphite sheets was in the range of 720 to 760 mm. 2 / s, and the foam thickness range was measured to be 70-85 μm.

[0113] The thermal diffusion coefficient was measured in the planar direction by the Laser Flash method using a measuring device (Netsch, LFA467), and the foam thickness was measured by a Digital Micrometer (Standard-type, Mitutoyo).

[0114] As shown in Figure 4, the thermal diffusion coefficient showed a tendency to decrease as the specific gravity of the second plasticizer (TCP) increased in the total plasticizer content (content of the first plasticizer + content of the second plasticizer).

[0115] In contrast, the foam thickness showed a tendency to increase as the specific gravity of the second plasticizer (TCP) increased in the total plasticizer content (content of first plasticizer + content of second plasticizer).

[0116] Furthermore, in the case of Comparative Example 3 containing only the second plasticizer, the graphite sheet produced had more bright spots than the graphite sheet produced in Examples 1 to 4, and the surface quality of the graphite sheet was reduced.

[0117] The embodiments of the manufacturing method of the present invention are merely preferred embodiments that enable a person skilled in the art having ordinary skill in the art to easily carry out the present invention, and are not limited to the above-mentioned embodiments, and therefore the scope of the present invention is not limited thereby. Therefore, the true technical scope of the present invention must be determined by the technical ideas of the appended claims. In addition, it is obvious to a person skilled in the art that various substitutions, modifications and changes are possible within the scope of the present invention, and it is self-evident that the parts that can be easily modified by a person skilled in the art are also included in the scope of the present invention. [Industrial Applicability]

[0118] The present invention has an effect of providing a polyimide film which does not decrease in thermal diffusion coefficient and has a low mass loss rate upon carbonization and graphitization, a method for producing a graphite sheet from the polyimide film, and a graphite sheet having excellent appearance produced from the polyimide film.

Claims

1. comprising a first plasticizer and a second plasticizer, The molecular weight of the first plasticizer and the second plasticizer is 700 g / mol or less, The first plasticizer comprises triphenyl phosphate; the second plasticizer comprises tricresyl phosphate; For graphite sheet manufacturing, Polyimide film.

2. The difference in molecular weight between the first plasticizer and the second plasticizer is 150 g / mol or less. The polyimide film according to claim 1 .

3. The polyimide film contains 1.65 wt % or less of the first plasticizer and the second plasticizer based on the total content of the imidization catalyst contained in the polyimide film. The polyimide film according to claim 1 .

4. The weight ratio of the first plasticizer to the second plasticizer is 1:9 to 9:1; The polyimide film according to claim 1 .

5. The first plasticizer or the second plasticizer is The composition further includes any one selected from the group consisting of triphenylphosphine, resorcinol bis(diphenyl phosphate) and bisphenol A bis(diphenyl phosphate); The polyimide film according to claim 1 .

6. Dianhydride monomers including pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, oxydiphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or combinations thereof; and formed from diamine monomers including 4,4'-oxydianiline, 3,4'-oxydianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-methylenedianiline, 3,3'-methylenedianiline, or combinations thereof; The polyimide film according to claim 1 .

7. The elongation is 120% or more, The strength is 210 MPa or more, The residual amount upon thermal decomposition at 1000°C is 56% by weight or more, True density is 1.35 g / cm 3 That's all. The polyimide film according to claim 1 .

8. A method for producing a polyimide film according to any one of claims 1 to 7, comprising the steps of carbonizing, graphitizing, or carbonizing and graphitizing the polyimide film according to any one of claims 1 to 7. A method for manufacturing graphite sheets.

9. The thermal diffusion coefficient of the graphite sheet is 720 mm 2 The method according to claim 8, wherein the ratio of the stoichiometric ratio to the total stoichiometric ratio is 1 / s or more.

Citation Information

Patent Citations

  • Electrostatic adsorption resistant polyimide film and preparation method thereof

    CN105368048A

  • Graphite sheet polyimide film and production method thereof

    JP2016017169A

  • Polyimide film and manufacturing method thereof

    KR1020210026053A

  • KR2017-0049912

  • Method for manufacturing graphite sheet and polyimide film for graphite sheet

    WO2019187621A1